“If you sell land, you eat land”: change and continuities in the haciendas of the Amaime River basin, Cauca Valley, Colombia, 19th century - Giraldo Hoyos, Juan Martín (Universidad Pedagógica y Tecnológica de Colombia, 2019)
This paper explores the land tenure and land use dynamics in Cauca River Valley’s haciendas throughout the second half of the 19th century, based on cases in the basin of the Amaime River, Cauca River’s tributary. With the aim to challenge the narrative of social and economic stagnation created about this region, this study analyzes the dynamics of spatial transformation in selected landed states, revealing their systematic spatial and productive transformation in line with the historical process of nineteenth-century liberalism. For which diverse primary sources were consulted, including correspondence letters, historical cartographies and notarial documents. The use of a Historic Geographical Information System allowed to georeference notarial data to analyze and display land tenure spatial changes within the frame of study. The cases of the haciendas La Concepción and La Torre show, from opposite trajectories, that since the 1850s significant processes of productive reorientation and social diversification took place in this valley.